2020
DOI: 10.1038/s41398-020-01075-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in cortical folding patterns for prenatal predispositions to hallucinations in schizophrenia

Abstract: All perception is a construction of the brain from sensory input. Our first perceptions begin during gestation, making fetal brain development fundamental to how we experience a diverse world. Hallucinations are percepts without origin in physical reality that occur in health and disease. Despite longstanding research on the brain structures supporting hallucinations and on perinatal contributions to the pathophysiology of schizophrenia, what links these two distinct lines of research remains unclear. Sulcal p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 73 publications
5
18
0
Order By: Relevance
“…One's cultural background may additionally influence the way that memories are reconstructed: for instance, individuals from East Asian and Western cultures differ in the way that they incorporate contextual and self-relevant details in memory (reviewed by Gutchess & Huff 2016), suggesting a basis for cultural differences in the subjective experience of memory. Conversely, the link discussed above between paracingulate sulcus reductions and hallucinations in schizophrenia has been found to generalize across patients from Australia, the United Kingdom, and China (Garrison et al 2015;Rollins et al 2020).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One's cultural background may additionally influence the way that memories are reconstructed: for instance, individuals from East Asian and Western cultures differ in the way that they incorporate contextual and self-relevant details in memory (reviewed by Gutchess & Huff 2016), suggesting a basis for cultural differences in the subjective experience of memory. Conversely, the link discussed above between paracingulate sulcus reductions and hallucinations in schizophrenia has been found to generalize across patients from Australia, the United Kingdom, and China (Garrison et al 2015;Rollins et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…People with schizophrenia are often impaired on reality monitoring tasks (Bentall et al 1991;Brébion et al 2000), tending to misattribute imagined stimuli as real (Stephane et al 2010;Vinogradov et al 1997), an effect that is associated with reduced activity in anterior prefrontal cortex (Garrison et al 2017;Vinogradov et al 2008). Moreover, the occurrence of hallucinations in people with schizophrenia can be predicted on the basis of paracingulate sulcus length, with sulcal reductions in individuals with a history of hallucinations compared with those who received their diagnosis based on other symptoms (Garrison et al 2015;Rollins et al 2020) (Figure 3D).…”
Section: Hallucinations and Schizophreniamentioning
confidence: 99%
“…detailed in Supplementary Table 2. Following cluster assignment, correlation values for each brain region within a cluster were then averaged, similar to that described previously [13]. Mean correlation values were then compared between treatment conditions and sex using Kruskal-Wallis non-parametric testing, with corrections for multiple comparisons using a two-stage step-up FDR method at a level of 5%.…”
Section: Structural Covariancementioning
confidence: 99%
“…Another brain area associated with hallucinations is the superior temporal sulcus. For example, a reduced depth of this sulcus is observed in patients with auditory hallucinations [36]. Some studies revealed that focal decreased gyrification might lead to hallucinations, but also global reduction of this process might play an important role [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a reduced depth of this sulcus is observed in patients with auditory hallucinations [36]. Some studies revealed that focal decreased gyrification might lead to hallucinations, but also global reduction of this process might play an important role [36,37]. Decreased cortical folding was also observed in patients with obsessive-compulsive disorder (OCD).…”
Section: Discussionmentioning
confidence: 99%